2023
DOI: 10.1097/aog.0000000000005093
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Coronavirus Disease 2019 (COVID-19) mRNA Vaccines During Lactation

Abstract: COVID-19, coronavirus disease 2019; CDC, Centers for Disease Control and Prevention; ACOG, American College of Obstetricians and Gynecologists; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The Centers for Disease Control and Prevention and the American College of Obstetricians and Gynecologists recommend that lactating patients receive COVID-19 mRNA vaccines, and there is no evidence that breast milk from lactating individuals who have received COVID-19 mRNA vaccines causes harm to lactating infants. [56][57][58] However, the antibody response in this population after vaccination is also a concern. At present, some prospective cohort studies have reported the response to vaccination in such populations.…”
Section: People With Immune Deficiency Caused By Underlying Diseasesmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention and the American College of Obstetricians and Gynecologists recommend that lactating patients receive COVID-19 mRNA vaccines, and there is no evidence that breast milk from lactating individuals who have received COVID-19 mRNA vaccines causes harm to lactating infants. [56][57][58] However, the antibody response in this population after vaccination is also a concern. At present, some prospective cohort studies have reported the response to vaccination in such populations.…”
Section: People With Immune Deficiency Caused By Underlying Diseasesmentioning
confidence: 99%
“…However, scientific research has already uncovered a complex mechanism that regulates the level of immune components in maternal milk [8,9].The children's understanding of the influence of immunizing their mothers with the COVID-19 vaccine on their safety is the most essential aspect of the mothers' immunization efficacy as a child protection strategy. It raises several problems about when daily vaccines should be administered, how long should it take between consecutive doses, and if boosters are necessary to maintain the antigen population of human milk at optimal levels [10]. In addition, researchers explore for a link between the kind and duration of antibodies in human milk and other vaccinations such as mRNA, viral vectors, and dead viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine-induced immunity in pregnant and lactating women and their newborns has been widely assessed: immune transfer of neutralizing anti-Spike IgG and T-cells from the mother to the newborn occurs through the placenta and breastmilk, which foster the breastfeeding infant’s developing immune system, suggesting a potential prevention of infection [ 10 , 19 , 20 , 21 ]. Current studies show that the pregnancy trimester does not affect SARS-CoV-2 antibody production [ 22 ].…”
Section: Introductionmentioning
confidence: 99%